Identifikasi Keanekaragaman Tumbuhan Obat – obatan di Kawasan Desa Pataruman, Kecamatan Cihampelas, Kabupaten Bandung Barat - Gina Satira; Ingrie Laila; Pundy Vidiapuri; Ateng Supriatna (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Medicinal plants are plants that are used by the community to improve the ability to live a healthy life. This public belief that has been carried out from generation to generation has been scientifically proven. Rural communities generally plant various types of plants, both seasonal and perennials, in their yards, which are commonly referred to as living barns, living stalls and living pharmacies. This research was conducted in one of the house yards in Pataruman village, Cihampelas sub-district, Bandung Regency. By identifying medicinal plants based on their morphology and literature studies. The results of this research obtained 6 plant species, namely Katuk, Betel, Bandotan, Honje, Ki Edi, and Aloe Vera. The substances contained in these plants are very beneficial for health, such as flavonoids, alkaloids, tannins, vitamins A, B, C and others. These benefits include antidiabetic, anti-inflammatory, analgesic, antioxidant, and can increase breast milk production.